Tailorable Fe nanostructures and magnetic anisotropy in (La0.5Sr0.5FeO3)1-x:Fex thin films integrated on SrTiO3 and silicon substrates - M. Kalaswad; B. Zhang; Han Wang; X. Wang; J. Huang; H. Wang (Materials Today Advances, 2020)
Vertically aligned magnetic nanostructures embedded in oxide matrices are an attractive framework for exploring anisotropic properties with potential applications in devices such as magnetic tunnel junctions. Magnetic response can easily be tuned through the growth of self-assembled ferromagnetic nanostructures in oxide-metal nanocomposite thin films. Here, oxide-metal (La0.5Sr0.5FeO3)1-x:Fex (LSFO1-x:Fex) nanocomposite thin films with various molar concentrations of Fe (x = 0.3, 0.4, 0.5) are grown by pulsed laser deposition under reducing conditions. The morphology and magnetic properties of Fe nanostructures are investigated to demonstrate tailorable magnetic anisotropic properties. Increasing the concentration of Fe in the nanocomposites has been found to reduce the aspect ratio of Fe nanostructures thus leading to a lower magnetic anisotropy. In addition, LSFO0.7:Fe0.3 thin films are successfully integrated on silicon substrates, which is a critical step toward realizing the proposed device applications. This study demonstrates oxide-metal LSFO1-x:Fex nanocomposites as a unique platform for tailoring magnetic properties and future integration of magnetic nanostructures with tunable magnetic anisotropy for device applications.